ANALISA PERBANDINGAN PEMBIAYAAN HUNIAN SYARIAH DENGAN AKAD MURABAHAH DAN AKAD MUSYARAKAH PADA BANK MUAMALAT (STUDI KASUS PADA BANK MUAMALAT SURABAYA) - ROSYIDA, EVA (Jurnal Akuntansi AKUNESA, 2013)
One of consumer financing product from Bank Muamalat is HunianSyariah Financing. Bank Muamalat gives two options of contract, that isMurabahah contract (Sale and Purchase) and Musyarakah contract (LeaseCooperation). In this journal, the author try to analyze the comparison of HunianSyariah Financing with Murabahah contract and Musyarakah contract at BankMuamalat. The methods that used is descriptive qualitative. The results is atMurabahah contract, bank buy a house for customer then the customer payinstallment payment every month. While in Musyarakah contract occurred jointventure between bank and customer, where customer has to pay to the bank withthe same portion belonged to the bank.Key words : Hunian Syariah Financing, Murabahah, Musyarakah, BankMuamalat